Orthodontic Treatment as a Protective Factor for Dental Caries Experience and Severity: A Population-Based Study - Ahmed A. Alsulaiman (International Journal of Dentistry)
Objective. The aim of this study was to assess the effects of orthodontic treatment on the experience, prevalence, and severity of dental caries later in life in a representative sample of U.S. adults. Methods. Using a population-based study design, data from 9,486 participants in the third National Health and Nutrition Survey (NHANES), including self-reported information on the history of orthodontic treatment and its timing, were obtained. Caries experience and prevalence was assessed using the decayed (DT) and filled (FT) teeth indices (i.e., DT > 0, FT > 0, and their aggregate DFT > 0). Severe dental caries experience and prevalence was defined as DT > 2, FT > 11, and DFT > 12. Unadjusted and adjusted logistic regression models that accounted for the complex sampling design were used to assess the association between orthodontic treatment and dental caries experience, prevalence, and severity. Statistical significance was set at a P value of less than 0.05. Results. The history of orthodontic treatment was reported in 19.62% of the adults. Around 94% of participants had at least one decayed or filled tooth (DFT > 0), and 21.09% met the aggregate DFT criterion for severe caries (DFT > 12). After controlling for confounding variables, a reported history of orthodontic treatment was found to significantly decrease the odds of DT > 0, DT > 2, FT > 11, and DFT > 12 (odds ratios (OR) = 0.41, 0.36, 0.74, and 0.60, respectively). Conclusion. A history of orthodontic treatment was a protective factor for untreated dental caries, in assessments of the severity and prevalence of dental caries experience.